"Face the Bullet, Spare the Rod?" Evidence from the Aftermath of the Shining Path Insurgency - Alvaro Morales; Prakarsh Singh (Institute for the Study of Labor (IZA), 2016)
We investigate whether violence occurring outside the confines of a home can alter intra-household violence inter-generationally. This paper is the first to explore whether exposure to violence from an armed conflict affects the later use of physical punishment as a child discipline method. Our identification strategy relies on the spatial and temporal variation of the Peruvian civil conflict that occurred between 1980 and 2000. We find that a mother exposed to an additional one hundred violent conflict-related events in her district is 3.4-3.8 percentage points less likely to physically punish her children. This effect is equivalent in magnitude to an additional 10 years of education. We find suggestive evidence that the conflict could have increased parenting knowledge and support. Communities that experienced higher levels of conflict violence saw greater increases in social spending and had more health resources in the post-conflict period. Additionally, we find women's conflict exposure is associated with a higher likelihood of accessing these resources.
Keywords: J13; D1; J16; 330; domestic violence; civil conflict; physical child abuse; Peru